Parcelamento da adubação nitrogenada no feijão em sucessão a sistemas de cultivo com milho e Urochloa ruziziensis em plantio direto - Flôres, Jordana de Araujo [UNESP] (2015)
The objective of this worky was to evaluate the influence of splitting the nitrogen topdressing in productive and qualitative attributes of the bean in succession to corn and Urochola ruziziensis grown exclusively and mixed. The experiments was carried out in the agricultural years 2012/13 under split plot design in randomized blocks, with four replications. The plots were formed by three cropping systems constituted by the commom bean (IAC Imperador) succession to maize and Urochloa ruziziensis in exclusive and intercropped crops. The subplots had been constituted for eight nitrogen split, rate 90 kg ha-1 via urea, applied as topdressing at the formation of the first trifoliate (V3), in the presence of the third trifoliate leaf (V4) and the pre-flowering (R5), 30+60+00, 60+30+00, 30+00+60, 60+00+30, 00+60+30, 45+45+00, 00+45+45 e 45+00+45, single dose V4 (00+90+00) and without this nutrient topdressing application, totaling 30 treatments. The amount of straw and soil cover in corn and U. ruziziensis are within the recommended system for tillage.The bean in succession to exclusive U. ruziziensis presents higher grain yield. The cultivation of beans after the consortium between corn and U.ruziziensis promotes higher content of crude protein and maximum moisture grain. The nitrogen splitting topdressing does not change the qualitative attributes of the bean grains